GE_GERICHTE P/12242/2018 vom 18. August 2022 - GE Cour de justice (2022)
QUALITÉ POUR AGIR ET RECOURIR;ACTIONNAIRE;FAUX MATÉRIEL DANS LES TITRES;ESCROQUERIE;FAUX TÉMOIGNAGE | CPP.382; CP.251; CP.146; CP.307